Rainwater Harvesting for Agriculture and Water Supply - Zhu, Qiang.; Zhu, Qiang.; Gould, John.; Gould, John.; Li, Yuanhong.; Li, Yuanhong.; Ma, Chengxiang.; Ma, Chengxiang. (Springer Singapore : Imprint: Springer, 2015)
This book offers key resource materials developed for an international training course on Rainwater Harvesting and Utilization hosted annually by the Gansu Research Institute for Water Conservancy in Lanzhou, China since 2003. Topics cover the design, construction and management of rainwater harvesting systems for domestic water supply and supplementary irrigation, rainwater quality issues and runoff farming. It presents case studies from successful rainwater-harvesting projects both in China and around the globe, and provides readers with essential information and inspiration alike. It is a valuable resource for researchers, practitioners and students in the area of water management, agriculture and sustainable development. Qiang Zhu is a research professor at Gansu Research Institute for Water Conservancy, Lanzhou, China;  John Gould is a rainwater harvesting consultant based in Christchurch, New Zealand; Yuanhong Li is a research professor at Gansu Research Institute for Water Conservancy, Lanzhou, China; Chengxiang Ma is an engineer at Gansu Research Institute for Water Conservancy, Lanzhou, China.